2014
DOI: 10.1038/ncomms4499
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic optical holography for rapid nanoimaging

Abstract: Holography has paved the way for phase imaging in a variety of wide-field techniques, including electron, X-ray and optical microscopy. In scanning optical microscopy, however, the serial fashion of image acquisition seems to challenge a direct implementation of traditional holography. Here we introduce synthetic optical holography (SOH) for quantitative phase-resolved imaging in scanning optical microscopy. It uniquely combines fast phase imaging, technical simplicity and simultaneous operation at visible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 67 publications
2
76
0
Order By: Relevance
“…The h-BN (7 nm)-graphene-h-BN (46 nm) stack assembled by the polymer-free van der Waals assembly technique 22 lies on top of an oxidized silicon wafer, used as a backgate. This stack is etched into a triangle and is electrically side-contacted with metal electrodes 22 .We image propagating plasmons with a scattering-type scanning near-field optical microscope 25,26 (s-SNOM), similar to several recent studies of graphene plasmons 23,24,[27][28][29][30][31] . A schematic of the s-SNOM interacting with the graphene device is shown in Fig.…”
mentioning
confidence: 97%
“…The h-BN (7 nm)-graphene-h-BN (46 nm) stack assembled by the polymer-free van der Waals assembly technique 22 lies on top of an oxidized silicon wafer, used as a backgate. This stack is etched into a triangle and is electrically side-contacted with metal electrodes 22 .We image propagating plasmons with a scattering-type scanning near-field optical microscope 25,26 (s-SNOM), similar to several recent studies of graphene plasmons 23,24,[27][28][29][30][31] . A schematic of the s-SNOM interacting with the graphene device is shown in Fig.…”
mentioning
confidence: 97%
“…In addition, in synthetic holography, the key element is the presence of a synthetic reference wave, analogous to a plane reference wave in wide-field off-axis holography, that is generated by adding a linearly moving reference mirror to the microscope setup. 8 The latter introduces a linear temporal/spatial modulation in the phase of interference term. In the proposed system, since no reference beam can be defined, the temporal/spatial phase modulation is synthetized inside the phase ϕ of interference term γ by means of a synthetic tilt of the sample.…”
mentioning
confidence: 99%
“…[4][5][6][7] Although the features of wide-field digital holography have confirmed this technique as a relevant tool for imaging, only recently this method has been implemented in optical scanning microscopy. 8 In the latter, named synthetic optical holography (SOH), a point detector is employed, replacing CCD cameras, in order to encode the phase across the whole image. It was demonstrated that SOH is a method technically simple and fast for phase imaging.…”
mentioning
confidence: 99%
“…The radar community developed an analogous concept [3] that instead assembles a hologram pointwise using a local electronic oscillator as a reference to avoid the impossible task of physically interfering the object field with a similarly scaled reference. We here introduce synthetic optical holography (SOH) [4], which uses a similar concept to produce an optical digital hologram. This is desirable in cases where an appropriate reference field is inconvenient or impossible to produce using conventional optics.…”
Section: Introductionmentioning
confidence: 99%